C9ORF72 G4C2-repeat expansion and frontotemporal dementia first reported case in Argentina. Issue 3 (3rd May 2016) - Fernández Suarez, M.; Surace, Ezequiel; Harris, P.; Tapajoz, F.; Sevlever, G.; Allegri, R.; Russo, G. N.
ABSTRACT: We present a female patient aged 51 who developed behavioral disorders followed by cognitive impairment over 3 years. Neuropsychological, neuropsychiatric, and radiological features suggested a probable behavioral variant of frontotemporal dementia (bvFTD). A family history of amyotrophic lateral sclerosis and parkinsonism suggested the hexanucleotide repeat expansion G4 C2 in C9ORF72 . We set up a two-step genotyping algorithm for the detection of the expansion using fragment-length analysis polymerase chain reaction (PCR) and repeat-primed PCR with fluorescent primers. We confirmed the presence of an expanded G4 C2 allele in the patient. This represents the first documented case of bvFTD due to a C9ORF72 expansion in Argentina.